Metabolic and energetics characterization and gender comparison in prepubertal karate practitioners - VencesBrito, António M.; Rodrigues-Ferreira, Mário A.; Milheiro, Vitor; Branco, Marco; Mercê, Cristiana; Seabra, Ana Paula; Catela, David (Revista de Artes Marciales Asiáticas, 2019)
The number of children practicing karate is constantly increasing. It is necessary to provide correct information to the karate masters/coaches about this specific population, so they can properly develop karate training processes without causing any harm to practitioners but, on the contrary, contribute to the harmonious development of children and youths. This study was carried out with twenty-one prepubertal karate practitioners, male and female. They were analyzed on their maturational development, metabolic and energetic behavior in an incremental test until exhaustion. Only the energetic variables presented significant differences between gender, so it seems that the karate practice has a similar metabolic impact in the development of the prepubertal karate practitioners of both genders.